Vacuum degasifier: comprehensive modelling and simulation - Hussain, Mohd Azlan (Elsevier, 2001)
A vacuum degasifier is used to remove dissolved gases in water for many industrial processes. The present industrial design of these vacuum degasifiers use simple methods and formulae, which normally involve the removal of common gases such as oxygen and carbon dioxide only. In this study, a comprehensive modelling and computer-aided design procedure is presented. It incorporates the removal of both non-ionized gases (i.e. oxygen, argon, nitrogen and methane) and ionized gases (i.e. carbon dioxide, hydrogen sulphide and ammonia) in various applications. The vacuum pumps used are the NASH liquid ring types and the packings are of the MASPAC model types.